The politics as pollution. Feminisms and left militancies in the seventies - Martínez Prado, Natalia (Centro de Estudios Avanzados, 2021)
In this article I analyse the emergence of the most recognised feminist organisations in Argentina in the 1970s, in order to analyse how they were conditioned by party politics and the prevailing Marxist ideology of the time. By tracing a common ground of significance, shaped by the radicalised horizon represented by the left, I try to point out their meaningful distinction from a relational, differential and antagonistic inscription. In particular, I look at the way in which "consciousness-raising" groups were established as a methodology unique to feminisms and the effects of the principle of "horizontality" in the definition of the identity of feminist politics.